A Rare Occurrence of Choledochoduodenal Fistula in a Patient with Obstructive Jaundice Secondary to Pancreatic Cancer after Biliary Stent Placement - Sherkar, Dr Nitin; Takarkhede, Dr. Pankaj; Mehra, Dr Bhupendra; Dubhashi, Dr Siddharth; Sawarkar, Dr Prashant (International Journal of Innovative Research in Medical Science, 2025)
Intestinal perforation post biliary stent placement is extremely uncommon and is induced by different factors. Choledochoduodenal fistula (CDF) caused by biliary stent-induced perforation is also rare occurrence. We present a case of obstructive jaundice due to pancreatic cancer with a development of CDF following biliary stent placement and was managed by Whipple’s procedure successfully. CDF could have resulted from a bile duct rupture induced by pressure necrosis and inflammation generated by direct contact between the common bile duct and the stent's edge.